COMBINING LIDAR AND TLS DATA TO GENERATE DTM OF ITB JATINANGOR CAMPUS - Dwipriadi, Putra
In carrying out development planning one of the most important things is to know the condition of the land surface in the area of the development plan that can be seen through the DTM (Digital Terrain Model). DTM can be formed from UAV LIDAR (Unmanned Aerial Vehicle Light Detection and Ranging) data and TLS (Terrestrial Laser Scanner). Scanning using UAV LIDAR has the disadvantage that not all emitted waves can penetrate the area with a dense canopy. These deficiencies can be complemented by TLS scanning in areas with dense vegetation. The purpose of this study is to determine the right method for combining LIDAR and TLS data in making DTM of ITB Jatinangor campus and analyzing the differences between DTM produced before and after the combination of UAV LIDAR and TLS data in the ITB Jatinangor campus area The methodology in this research is to do the acquisition and processing of cloud point data generated from LIDAR and TLS scanning. The combination process is done by registering globally all cloud points resulting from the scanning of the UAV LIDAR and TLS. The next process is to compare data before and after the combination of UAV LIDAR and TLS data based on differences in cloud point density, differences in surface height resulting from the TIN method, and differences in contours. The value of cloud point density before the combination is worth 328 points / 25 m2 and increases after the combination becomes 2113 points / 25 m2. Also there are differences in height before and after a combination that can be seen from the standard deviation of 0.727 m. The increase in cloud point density and the presence of the standard deviation values indicate an increase in surface quality after a combination is made.